Construction work and the mobility imperative: changing rhythms along uncertain paths. Issue 2 (4th May 2021) - Barber, Lachlan B.; Neis, Barbara
ABSTRACT: This article considers experiences of rhythmic change related to employment-related geographical mobilities in parts of the Canadian construction industry. Drawing on Lefebvrian rhythmanalysis and aspects of time-geography, we consider how workers and their loved ones negotiate changes in space-time patterns across careers in industrial construction, especially work at projects tied to resource development and extraction. Data are derived from in-depth career history interviews conducted with workers in the Canadian province of Newfoundland and Labrador between 2014 and 2018. Three "career path" cases illustrate mobile rhythms of differently positioned workers from their entry into construction to their career stage at the point of the interview, ranging from apprenticeship through mid-career journeyed to retirement. These workers pursue training and jobs involving variable mobilities between home and work across shifting locations. We contribute to recent efforts to highlight the compatibility of rhythmanalysis with an expanded, feminist, biographical approach to time-geography, and the applicability of such an approach for the applied study of mobilities. We also respond to recent calls to study experiences of rhythmic change in the lives of mobile and migrant workers. Findings reveal that changes in mobile rhythms may be small and incremental, as in the case of schedule or rotation adjustments, or sweeping and large scale, as in the case of shifts from working locally to working in distant locations amidst the disruptions caused by the COVID-19 pandemic. Experiences of disruption and responses to change are personal and familial, conditioned by social positions and subjectivities.